The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.21273/hortsci.36.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 15N-Labeled Fertilizer Applied to Pecan: A Case Study

Abstract: From March through June 1996, 15N-labeled fertilizer was applied to mature pecan trees [Carya illinoinensis (Wangehn.) K. Koch] in a commercial orchard to determine the fate of fertilizer-N in the tree and in the soil directly surrounding the tree. The concentrations of 15N and total N were determined within various tissue components and within the soil profile to a depth of 270 cm. By Nov. 1996, elevated levels of 15 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…However, Li et al (2003) reported that a water limitation and a high N level can lead to a poor N efficiency for spring wheat. Moreover, low soil moisture can adversely affect fertilizer mobility in the soil, leading to a decrease in its uptake by the plant (Kraimer et al, 2001;Yuan et al, 2005). In the present study, the soil water status affected the N ratio between the fertilizer and soil, showing that a water deficit decreases the proportion of N derived from the fertilizer, while increasing N derived from the soil.…”
Section: Discussionmentioning
confidence: 51%
“…However, Li et al (2003) reported that a water limitation and a high N level can lead to a poor N efficiency for spring wheat. Moreover, low soil moisture can adversely affect fertilizer mobility in the soil, leading to a decrease in its uptake by the plant (Kraimer et al, 2001;Yuan et al, 2005). In the present study, the soil water status affected the N ratio between the fertilizer and soil, showing that a water deficit decreases the proportion of N derived from the fertilizer, while increasing N derived from the soil.…”
Section: Discussionmentioning
confidence: 51%
“…Tree weights of the three destructively sampled trees averaged 2% less than weights predicted by equations of King and Schnell (1972), indicating that tree weight was estimated with reasonable accuracy by the equations. Kraimer et al (2001) reported that tree weights of pecan were 8.6% less than the weight estimated using King and Schnell's equations. Our tree weights may agree more closely with the calculated weights because the trees of Kraimer et al (2001) were hedged, whereas ours were not.…”
Section: Methodsmentioning
confidence: 90%
“…Biomass of the perennial tree components was estimated using equations of King and Schnell (1972). These equations were used by Kraimer et al (2001) to estimate pecan weight in a New Mexico study. To confirm these equations and develop an equation to estimate leaf mass, three 15-year-old 'Maramec' trees spaced 10.7 × 10.7 m apart, growing on a Port silt loam (fine-silty, mixed, superactive, thermic Cumulic Haplustolls) at the Pecan Research Station near Sparks, Okla. were harvested on 16 to 23 Oct. 1998.…”
Section: Methodsmentioning
confidence: 99%
“…To estimate N storage pools and N distribution in different organs, the utilization of 15 N is the main method used in fruit trees (Kraimer et al, 2001). This procedure was used to study N dynamics in traditional blueberry varieties (Retamales and Hanson, 1989;Chuntanaparb and Cummings, 1980;Merhaut and Darnell, 1995).…”
mentioning
confidence: 99%